How to Reduce Stress on the Pedicle Screws in Thoracic Spine? Importance of Screw Trajectory: A Finite Element Analysis - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2017)
AIM: To investigate the biomechanical comparison of thoracic transpedicular screw trajectories on the sagittal plane. MATERIAL and METHODS: A three-dimensional, non-linear finite element analysis (FEA) model of T8 through T9 was used. Anatomic trajectory (AT) and Straightforward trajectory (ST) models of the transpedicular screws were used in the intact FEA model. The von-Mises stress and range of motion (ROM) of the transpedicular screws were evaluated. RESULTS: The difference in ROM between both techniques was negligible. In lateral bending and axial rotation, FEA showed decrease in stress by 25% and 8%, respectively, when pedicle screws were placed using AT. CONCLUSION: AT decreased the von-Mises stress of the pedicle screws, thereby reducing the rates of screw breakage and fatigue risks. In addition, we believe that AT could protect against screw loosening because the von-Mises stress of the internal fixation was scattered.
Keywords: Finite element; Screw fixation; Spine; Thoracic; Trajectory; FIXATION; STRENGTH; INSTRUMENTATION; FUSION; MODEL